Synthesis and characterization of thermochromic metal organic nanofibrils based on copper - Hu, Carl Lawrence L. (Animo Repository, 2016)
Metal organic frameworks are interesting materials with varied potential applications. In the present study, the synthesis of copper diacid nanoparticles using conventional coordination chemistry in a diffusion controlled growth procedure is reported. Five different diacids were used as a ligand and copper (II) was used as the metal to yield polymeric nanofibrils. Products were characterized by Melting Point Apparatus, Scanning Electron Microscope Energy Dispersive X-ray (SEM-EDX), Fourier Transform-Infrared Spectroscopy (FT-IR), Thermogravimetric Analyzer (TGA), X-ray diffraction measurements (XRD), and Transmission electron microscope (TEM). Various characterization results revealed the formation of new complexes. Moreover new stable thermochromic materials are discovered, indicating that copper-based complexes show excellent potential to be developed for a variety of applications that includes moisture sensing.